ANALYSIS OF HEAT TRANSFER IN A HEATED TUBE WITH A DIFFERENT TYPED DISC INSERTION - Turan, Betul; Öztop, Hakan Fehmi (Vinca Inst Nuclear Sci, 2012)
Heat transfer and fluid flow can be controlled in a tube by inserting different typed passive elements. The main objective of this study is to control heat transfer and fluid flow using cutting edged disc in pipe. Governing equations of laminar, 2-D flow is solved via finite volume technique. The disc is adiabatic and its thickness is 5 mm. It is located into axial axis of the tube. Three cases were applied based on the type of the disc as inclination angle of the top side is 45 degrees and 0 degrees. Calculations were performed for different Reynolds number in the range of 335 < Re < 845. Three cases were tested based on types of discs. It is observed that each position exhibits different heat transfer ratio according to studied Reynolds number. The highest heat transfer is formed when inlet flow impinges to flat side of the cutting edged baffle.
Keywords: heat transfer enhancement; disc; numeric; fluid flow